-5x-4(1-2x)=14+3x

Simple and best practice solution for -5x-4(1-2x)=14+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-4(1-2x)=14+3x equation:



-5x-4(1-2x)=14+3x
We move all terms to the left:
-5x-4(1-2x)-(14+3x)=0
We add all the numbers together, and all the variables
-5x-4(-2x+1)-(3x+14)=0
We multiply parentheses
-5x+8x-(3x+14)-4=0
We get rid of parentheses
-5x+8x-3x-14-4=0
We add all the numbers together, and all the variables
-18!=0
There is no solution for this equation

See similar equations:

| 21=9+3(h-6) | | -11=w/3+-10 | | 5/3x−3=241 | | -a/6+7=-2 | | 5/4(x+5/2)=-25/8 | | b/2-3=-15 | | 53x−3=241 | | 13y^2-38y-3=0 | | p/4-5=9 | | 11+x=-x-5 | | 7b-24+2b= | | [X(x+1)})/2=276 | | (7x×6)×(9x-2)=68 | | 3x-24=7x+28 | | 4k+14=78 | | 11+x=-3x-5 | | w/15-8=-5 | | -18x+(-65)+33x=10x-9-(-6) | | 256=3^x | | 3/5x=9/70 | | 2x-50°=+10°=0 | | -42=-7+5m | | 9m–15–2m=6m–1‒m | | 9^(-4x)=15 | | 11+x=4x-5 | | 6w+8w=208 | | [x(x+1)=552 | | 3(2x–5)=2(4x+3) | | 5x-6=-4+3x+24 | | n²+n-380=0 | | 24/4(/4)=x | | X.3(2x-5)=2(3x-2) |

Equations solver categories